Novel loss‐of‐function variants in DNAH17 cause multiple morphological abnormalities of the sperm flagella in humans and mice. Issue 1 (2nd November 2020) - Zhang, Beibei; Khan, Ihsan; Liu, Chunyu; Ma, Ao; Khan, Asad; Zhang, Yuanwei; Zhang, Huan; Kakakhel, Mian Basit Shah; Zhou, Jianteng; Zhang, Wen; Li, Yang; Ali, Asim; et al.
Abstract: Multiple morphological abnormalities of the flagella (MMAF) is a genetically heterogeneous disorder leading to male infertility. Recent studies have revealed that DNAH17 variants are associated with MMAF, yet there is no functional evidence in support of their pathnogenicity. Here, we recruited two consanguineous families of Pakistani and Chinese origins, respectively, diagnosed with MMAF. Whole‐exome sequencing identified novel homozygous DNAH17 variants, which led to loss of DNAH17 proteins, in the patients. Transmission electron microscope analyses revealed completely disorganized axonemal structure as the predominant anomaly and increased frequencies of missings of microtubule doublet(s) 4–7 in sperm flagella of patients. Similar to those found in patients, Dnah17 −/− mice also displayed MMAF phenotype along with completely disorganized axonemal structures. Clusters of disorganized microtubules and outer dense fibers were observed in developing spermatids, indicating impaired sperm flagellar assembly. Besides, we also noticed many elongating spermatids with a deformed nuclear shape and abnormal step 16 spermatids that failed to spermiate, which subsequently underwent apoptosis in Dnah17 ‐null mice. These findings present direct evidence establishing that DNAH17 is a MMAF‐related gene in humans and mice, extend the clinical interpretations of DNAH17 variants, and highlight an essential and complex role of DNAH17 in spermatogenesis. Abstract :